Determinan Kematian Bayi di 8 Kabupaten/Kota Provinsi Nusa Tenggara Timur Tahun 2018 – 2022 - Putri, Mutiara; Amalia, Fitri (FEB Universitas Sultan Ageng Tirtayasa, 2024)
Infant Mortality Rate (IMR) is one of the benchmarks for development progress in the health sector. In the Sustainable Development Goals, one of the targets is to achieve an Infant Mortality Rate of 12 per 1,000 live births. East Nusa Tenggara Province is one of the provinces with a high infant mortality rate. Therefore, this study aims to investigate the determinants of infant mortality in 8 Regencies/Cities in East Nusa Tenggara Province. The research method used is Panel Data Regression Analysis. The results of this study indicate that, partially, the Low Birth Weight (LBW) variable has a positive and significant effect, while BCG and DPT Immunization Coverage have a significant negative effect. The Female Labor Force Participation Rate has a significant positive effect, and the Number of Health Facilities (Puskesmas) has a significant negative effect on the Infant Mortality Rate. Meanwhile, the Health PDRB Per Capita variable has a negative and insignificant effect on the Infant Mortality Rate. Collectively, all independent variables have a significant effect on the Infant Mortality Rate.